Distinguishing intentions from desires: contributions of the frontal and parietal lobes. - Chiavarino, C; Apperly, I; Humphreys, G (2010)
The ability to represent desires and intentions as two distinct mental states was investigated in patients with parietal (N=8) and frontal (N=6) lesions and in age-matched controls (N=7). A task was used where the satisfaction of the desire and the fulfilment of the intention did not co-vary and were manipulated in a 2 × 2 set. In two experiments we show that lesions to the frontal lobe may impair the ability to deal with desires when their outcome is not congruent with that of the intention, and that parietal damage - especially if it encompasses the left temporo-parietal junction - may cause severe difficulties in the processing of both desires and intentions. The implications of the results for the neuropsychological and the developmental literature are discussed.